Measuring the effectiveness of ASEAN-5 initiatives from emerging market portfolio's perspective - Robiyanto Robiyanto; Bayu Adi Nugroho; Eka Handriani; Budi Frensidy (Cogent Business & Management, 2023)
ASEAN nations started ASEAN Economic Community (AEC) initiatives, with the goal of improving the economic movement in ASEAN. The initiative is expected to lead to higher integration in the regions. The objective of this research was to study the integration of equity markets in the ASEAN-5 nations (Indonesia, Malaysia, Singapore, Thailand, and the Philippines), particularly those involving the Indonesian stock market (Indonesia's economy is the largest in the region), and to analyze the diversification opportunities among ASEAN equity exchanges. Theoretically, capital markets in these nations should be more integrated following the introduction of AEC due to the integration of their economy and removal of several investment restrictions, including foreign ownership limitation. The data used was weekly data was used from January 2000 to June 2019, which was divided into four periods: pre-crisis, crisis, post-crisis and AEC. The methods used were DCC-GARCH, AG-DCC, volatility spillovers, Granger causality and diversification ratio from the mean-variance framework. The results showed robust evidence that there were still less integrated equity markets in ASEAN-5. The volatility spillover declined during the post-crisis period and was relatively stable during the AEC period. This result implies that ASEAN-5 initiatives have an impact on the capital markets. However, the implementation of the AEC is still far from successful since the equity exchanges have become less integrated than in the post-crisis period. Investors in Malaysia, Singapore, and the Philippines are encouraged to avoid investing heavily in Indonesia and Thailand equities during market turmoil since both are net contributors to volatility.
Keywords: G11; G15; 650; ASEAN Economic Community; diversification ratio; dynamic portfolio; emerging market; portfolio